PENGEMBANGAN HANDOUT BERNUANSA KONTEKSTUAL PADA MATERI SISTEM REGULASI MANUSIA UNTUK SMA - Cahyani, Ditha Amanda; ARDI, ARDI; Amri, Erismar (STKIP PGRI Sumbar, 2014)
ABSTRACT The less availability of handout for the Senior High School students had made the learning process not run as it was expected. Therefore, a creative and innovative effort was required to provide learning materials for Biology subject especially those related to Human Regulation System topic. The aim of this research was to produce a contextual-based handout for teaching Human Regulation System topic for Senior High School students and to reveal the validity and practicality of the product. This was a developmental research which used 4-D models. The research findings showed that the handout developed was valid. This could be seen from the result of the validation test done by the lecturers and teachers in which the validation score was 83,13%. The handout was also practical in which the score given by the teachers was84,71% and the score given by the students was 73,67%. Based on these results, it was concludedthat the contextual-based handout developed for teaching Human Regulation System topics forSenior High School students was valid and practical.